Exchanges Between Residents and Tourism Development (Malaysian Management Journal, 2001)
This qualitative study focused on utilizing a combination of social exchange and power theories to explain exchanges that occur between residents of Langkawi and tourism development on the island. The guiding question for this inquiry was "what role does power play in social exchanges that occur between residents and tourism development?" Findings revealed that social exchange is useful in examining residents' attitudes towards tourism as residents indeed based their attitudes on the evaluation of the returns that they receive from the exchanges. More importantly, the findings indicated that residents' general values, their dependence on tourism, and their ability and willingness to adapt moderated the influence of power an residents' evaluation of tourism impacts.